Control of bill-grasping aperture with varying food size in crows. Issue 7 (1st May 2019) - Matsui, Hiroshi; Izawa, Ei-Ichi
Abstract : Grasping movement in primates is known to be a visually guided behavior and the aperture of hand opening is adjusted to the target size on the basis of visual information. The analogous behavior can be found in birds, called 'pecking', consisting of head-reaching and bill-grasping. Bill-grasping has been investigated mainly in pigeons and an aperture adjustment as seen in primates has been reported. This study focused on kinematics of pecking in crows, known to possess dexterous visuomotor skills, to examine whether crows adjust the grasping aperture to food diameter with a kinematic mechanism similar to that in pigeons. The pecking at a small piece of food was video recorded to analyze the grasping aperture. The results showed that the grasping aperture was proportional to food diameter. Kinematic analysis showed that the aperture adjustment was mediated by grasping velocity and grasping duration, which is consistent with the findings of previous research on pecking in pigeons. However, the relative contribution of grasping velocity was much higher than that of grasping duration. Our findings suggest the different sensorimotor mechanisms to control bill-grasping between the avian species with different foraging ecology.